UNCOVER: A NIRSpec Census of Lensed Galaxies at z = 8.50–13.08 Probing a High-AGN Fraction and Ionized Bubbles in the Shadow - Seiji Fujimoto; Bingjie Wang; John R. Weaver; Vasily Kokorev; Hakim Atek; Rachel Bezanson; Ivo Labbe; Gabriel Brammer; Jenny E. Greene; Iryna Chemerynska; Pratika Dayal; Anna de Graaff; et al. (The Astrophysical Journal, 2024)
We present JWST NIRSpec prism spectroscopy of lensed galaxies at z ≳ 9 found behind the massive galaxy cluster Abell 2744 in the UNCOVER Cycle 1 Treasury Program. We confirm the redshift via emission lines and/or the Ly α break for 10 galaxies at z = 8.50–13.08 down to M _V = −17.3. We achieve a 100% confirmation rate for z > 9 candidates reported in H. Atek et al. Using six sources with multiple line detections, we find that offsets in redshift estimates between the lines and the Ly α break alone can be ±0.2, raising caution in designing future follow-up spectroscopy for the break-only sources with the Atacama Large Millimeter/submillimeter Array. With spec- z -confirmed sources in UNCOVER and the literature, we derive lower limits on the rest-frame ultraviolet (UV) luminosity function (LF) at z ≃ 9–12 and find that these lower limits agree with recent photometric measurements. We identify at least two unambiguous and several possible active galactic nucleus (AGN) systems based on X-ray, broad H β , high ionization lines, and excess in the UV LF. This requires the AGN LFs at z ≃ 9–10 to be comparable or even higher than the X-ray AGN LF estimated at z ∼ 6 and suggests a plausible cause of the high abundance of z > 9 galaxies claimed in the recent photometric measurements is AGNs. One UV-luminous source is confirmed at the same redshift as a broad-line AGN at z = 8.50 with a physical separation of 380 kpc in the source plane. These two sources show emission blueward of Ly α , indicating a giant ionized bubble enclosing them with a radius of 7.69 ± 0.18 pMpc. Our results imply that AGNs have a nonnegligible contribution to cosmic reionization.